ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN MAHASISWA PADA PENCAPAIAN TARGET PEMBELAJARAN PELAYANAN ASUHAN KESEHATAN GIGI DAN MULUT DI KLINIK JURUSAN KESEHATAN GIGI POLTEKKES MANADO - , Jeineke E. Ratuela, drg. Sri Widiati, MPH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: The achievement of learning targets for dental care at the Dental Health Department, Poltekkes of Manado indicated that in the academic year 2007/2008 there were 31.3% students who did not meet the targets of tooth extraction and in 2008/2009 there were 38.2% students who failed to meet the targets, much more than expected by the institution that none of the students failed to achieve the targets. This study was conducted to identify factors affecting the success of the students in meeting the learning targets of dental care at the Dental Health Department of Poltekkes, Ministry of Health, Manado. Methods: This is a cross-sectional study, with a total population sample of 44 students at the fifth semester, Dental Health Department of Poltekkes, Ministry of Health, Manado. The independent variables consist of internal factors, which are: 1) attitude, 2) intention, 3) motivation, and external fa tors, comprising: 1) parental and familial support, 2) lecturers/tutors, and 3) infrastructure and facilities. The dependent variable is the success of students in achieving the learning targets of dental care at the clinics of the Dental Health Poltekkes, Manado. Data were collected using questionnaire, and analyzed using logistic regression methods. Results: The results of logistic regression analyses show that motivation variable (OR = 73.562, CI = 3.872 â 1397.42, p = 0.004), infrastructure and facilities (OR = 26.533, CI = 2.176 â 323.540, p = 0.01) significantly associated with greater success in achieveng the learning objectives of dental health care in the Dental Health Department of Poltekkes Manado. While attitude (p = 0.369), intention (p = 0.296) and parental / family support (p = 0.296) were not associated with the achievement of learning objectives. Conclusion: 1) The higher motivation, the better the perceptions on the roles of teachers/tutors, and the better the perceptions on infrastructure and facilities, the higher the succes of students in achieving the learning targets of dental care at the clinics of Dental Health Department, Poltekkes, Manado